Making Canadian Indian Policy : The Hidden Agenda 1968-1970 - Weaver, Sally M. (Book collections on Project MUSE., 1981)
An analysis of the formulation of the Canadian government's White Paper on Indian policy based on interviews with individuals involved in shaping the policy, government documents and reports, and published materials.